Analisis Kemampuan Menghafal Al-Qur’an Juz 30 dengan Metode Talaqqi di Taman Pendidikan Al-Qur’an (TPQ) Babussalam Waru Sidoarjo - Inna Anzalna Ubudiyah H; Nadlif, Ainun (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyse the ability to memorise Qur'an Juz 30 with the talaqqi method at the Babussalam Waru Qur'an Education Park (TPQ) in Sidoarjo city. The talaqqi method, which emphasises direct interaction between teachers and students in the process of reading and repeating verses of the Qur'an, is believed to be able to improve the quality of memorisation and understanding of tajweed and makhraj. The research method used is descriptive qualitative with data collection through observation, in-depth interviews and documentation. The participants of this study involved santri aged between 7 and 12 years. The findings show that the talaqqi method is a commonly used approach in teaching Qur'an memorisation in TPQ. This study provides insight into the application of the talaqqi method in TPQ and its relevance in the context of Qur'anic education. It is hoped that the results of this study can make a practical contribution to the development of more effective Qur'ānic teaching strategies in TPQ and other Islamic educational institutions.